PENINGKATAN LITERASI DIGITAL GIZI ANAK BAGI ORANG TUA TK BHAYANGKARI SPN PADANG BESI MELALUI EDUKASI BERBASIS TEKNOLOGI - Christy, Tika; Safaria, Sayendra; Putri, Pristiyanilicia; Wendra, Yumai; Syafwan, Havid (Smart Education, 2025)
Abstract: Nutrition is an essential component of food that plays a significant role in maintaining health and supporting children's growth and development. Nutrients such as carbohydrates, fats, proteins, vitamins, minerals, and fiber contribute to enhancing the immune system, brain function, concentration, and energy levels in children. However, many kindergarten-aged children still experience a lack of focus, fatigue, and reluctance to engage in learning activities due to an unbalanced diet, high consumption of fast food, and limited parental understanding of balanced nutrition. In response to these issues, a community service program titled Enhancing Digital Nutrition Literacy for Parents of Kindergarten Students at Bhayangkari SPN Padang Besi was conducted to increase parents’ awareness of the importance of nutrition in early childhood. This program utilizes digital media such as animated videos and the easily accessible online application nutrysmart.id. The educational approach is interactive, encouraging parents not only to receive information but also to participate actively in discussions, hands-on practice, and comprehension assessments. The collaboration between schools and parents is expected to foster an environment that supports children in growing up healthy, intelligent, and ready to learn optimally. Keyword: nutrition, child growth and development, nutrition, digital literacy Abstrak: Nutrisi merupakan bagian penting dalam makanan yang berperan besar dalam menjaga kesehatan dan mendukung tumbuh kembang anak. Zat gizi seperti karbohidrat, lemak, protein, vitamin, mineral, dan serat berkontribusi dalam meningkatkan daya tahan tubuh, fungsi otak, konsentrasi, dan energi anak. Namun, masih banyak anak usia TK yang mengalami kurang fokus, mudah lelah, dan enggan belajar akibat pola makan yang tidak seimbang dan tingginya konsumsi makanan cepat saji, ditambah minimnya pemahaman orang tua mengenai gizi seimbang. Sebagai respons terhadap permasalahan tersebut, kegiatan pengabdian masyarakat bertema Peningkatan Literasi Digital Gizi Anak bagi Orang Tua TK Bhayangkari SPN Padang Besi dilaksanakan untuk meningkatkan pengetahuan orang tua tentang pentingnya gizi anak usia dini. Program ini menggunakan media digital seperti video animasi dan aplikasi nutrysmart.id yang mudah diakses secara online. Edukasi dilakukan secara interaktif agar orang tua tidak hanya menerima informasi, tetapi juga aktif berdiskusi, praktik langsung, dan mengevaluasi pemahaman. Kolaborasi antara sekolah dan orang tua diharapkan mampu menciptakan lingkungan yang mendukung anak agar tumbuh sehat, cerdas, dan siap mengikuti proses pembelajaran dengan optimal. Kata kunci: nutrisi, tumbuh kembang anak, gizi, literasi digital